KEANEKARAGAMAN JENIS PAKAN PADA LAMBUNG IKAN SEPAT SIAM (Trichogaster pectoralis) DI RAWA BANJIRAN DESA SEDANG KECAMATAN SUAK TAPEH KABUPATEN BANYUASIN - Ramadhan Ramadhan; Dian Mutiara; Indah Anggraini Yusanti (Universitas Sriwijaya, 2020)
The research on the diversity of feed types in the snakeskin gouramy hull was carried out in August to Desember in swamp flood, Sedang village, Suak Tapeh subdistrict, Banyuasin District. The method used is a field study with determination of stations carried out by purposive random sampling of 3 stations, namely the Nebong Kuning swamp station, the Poron swamp station and the Banan swamp station. This study aims to determine the diversity of feed types in the Sepat Siam fish hull in swamp flood, Sedang village, Suak Tapeh subdistrict, Banyuasin District. Based on the result of study found the type of feed in the sepat siam fish hull consisted of 2 groups, namely phytoplankton and zooplankton, which consisted of 5 classes namely Bacillariophyceae, Clorophyceae, Cyanophyceae, Crustaceae and Maxillopoda. Based on the diversity index of the type of snakeskin gouramy hull in Nebong Kuning Swamp station, the Poron swamp station and the Banan swamp station are included in the medium category which indicates that the habitat of the aquatic environment in which the snakeskin gouramy live namely swamp flood, Sedang village, Suak Tapeh subdistrict, Banyuasin District quite balanced and moderate ecological pressure. Keywords : Diversity, Feed, Flood Swamp, Hull, Snakeskin Gouramy